Gaza writes back ebook Short stories from young writers in gaza, palestine. - Alareer, Refaat (2014)
Gaza Writes Back is a compelling anthology of short stories from fifteen young writers in Gaza, members of a generation that has suffered immensely under Israel's siege and blockade. Their experiences, especially during and following Israel's 2008-2009 offensive known as "Operation Cast Lead", have fundamentally impacted their lives and their writing. Their words take us into the homes and hearts of moms, dads, students, children, and elders striving to live lives of dignity, compassion, and meaning in one of the world's most embattled communities. Readers will be moved by the struggles big and small that emerge from the well-crafted writing by these young people, and by the hope and courage that radiate from the authors' biographies.